letranger9000
New member
- Joined
- Oct 29, 2013
- Messages
- 2
f(x) = (√(1-2x))/(x^2 -9) + 3/(x^2 - 6x +8)
I thought:
x^2-9 -> (x-3)(x+3)
x^2-6x+8 -> (x-4)(x-2)
(√1-2x) (x-4)(x-2) + 3(x-3)(x+3)
---------------------------------------
(x-3)(x+3)(x-4)(x-2)
I just don't know what to do next and it just feels not right , please someone tell me how can I find the domain.
I thought:
x^2-9 -> (x-3)(x+3)
x^2-6x+8 -> (x-4)(x-2)
(√1-2x) (x-4)(x-2) + 3(x-3)(x+3)
---------------------------------------
(x-3)(x+3)(x-4)(x-2)
I just don't know what to do next and it just feels not right , please someone tell me how can I find the domain.
Last edited: